Effect of business risk and profitability on the capital structure of consumer goods companies listed on the Indonesia stock exchange before and during COVID-19 pandemic - DEDE NOFIALDI; AIMATUL YUMNA (Financial Management Studies, 2021)
The COVID-19 pandemic is a condition of the spread of SAR-CoV-2 (coronavirus) that attacks the human respiratory system. Indonesia's COVID-19 pandemic began when the first case was confirmed on March 2, 2020. The COVID-19 pandemic is often analogous to a "black swan" which means an unexpected event and has a significant impact on various sectors of human life. Therefore, companies need to regulate the balance of foreign capital and their capital to get an optimal capital structure to carry out company activities and achieve company goals amid the uncertainty of the COVID-19 pandemic. The population in this study is consumer goods companies listed on Indonesia Stock Exchange. With purposive sampling techniques obtaited 296 company sample data which is then processed using multiple linear analysis techniques. The results of this study include: (1) Business Risk and Capital Structure are negatively related insignificant. (2) Profitability and capital Structure are negative and significant.